Removal of antibiotic resistance genes during livestock wastewater treatment processes: Review and prospects - Huang, Feng; Hong, Yanting; Mo, Chunhao; Huang, Peier; Liao, Xindi; Yang, Yiwen (Frontiers in Veterinary Science, 2022)
Antibiotic resistance genes (ARGs) are emerging pollutants that have received extensive attention. Many different types of ARGs exist in livestock wastewater. If there are not effectively treated, they can not only threaten the healthy animal production, but also threaten public health and the ecological safety of surrounding environments. To address the high risk of ARGs livestock wastewater contamination, the removal effects of different types of wastewater treatment processes on ARGs and their influencing factors and mechanisms are reviewed herein. Additionally, the current problems associated with the removal of ARGs are discussed, and future research is proposed.